The Influence of Safety Briefing, Knowledge and Awareness of Occupational Safety and Health in Realizing Zero Accidents in the Work Environment - Widyasmoro, Adi; Elnardy, Mohammad Caesario; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (International Journal of Business, Law, and Education, 2025)
Occupational safety is an important aspect of the work environment, especially in high-risk building operations. This study is expected to provide recommendations for companies, especially shopping centers in Indonesia, to improve occupational safety programs. Increasing occupational safety knowledge and awareness is expected to create zero accidents. This study uses a quantitative approach with a survey research design. The data obtained will be analyzed using the SPSS application. The t-test was conducted to compare the average knowledge and awareness of occupational safety before and after attending a safety briefing. In addition, regression analysis will be used to identify factors that influence the increase in occupational safety knowledge and awareness. This study shows that there is a strong relationship (84%) between the implementation of safety briefings, knowledge, and awareness of K3 in realizing zero accidents in the work environment.